Development of a brain-wave driven computer game using brain-computer interface - Yeoh, Keng Wei (2015)
With the recent commercialisation of BCI devices, BCI-based games have recently been actively developed in order to provide users with a more realistic gaming environment. The objective of this project is to develop a brain-wave driven computer game using brain-computer interface. Many studies have been done in the domain of attention-based BCI computer games with emphasis on neurofeedback training of attention levels. However, there is a lack of study done in the domain of sustained attention. This project proposes a neurofeedback game in which the ability to lengthen sustained attention is set as the main challenge of the game. 10 subjects were gathered to play the game. It was found that improvements in duration of attentive levels were shown in Theta / Beta ratio readings of all subjects, with repeated game sessions. Further analysis of Theta / Beta ratio readings also showed that all subjects have improved in their duration of sustained attention. All in all, the game showed potential in training and lengthening the duration of sustained attention of an individual.